10-year trend analysis of atrioventricular node ablation in patient with atrial fibrillation: 2005–2014 United State hospitalization. (25th November 2020) - Wu, L; Narasimhan, B; Shah, A.N; Zheng, Y.Y; Bhatia, K; Kantharia, B
Abstract: Introduction: Atrial fibrillation (AF) ablation and Atrioventricular Node (AVN) ablation are both important non-pharmacological therapy of AF. In spite of increased availability of AF ablation data, that of AVN ablation per se is limited. Method: AF ablation was identified using ICD-9 procedure code with principle diagnosis of AF from United States National Inpatient Sample database 2005–2014. From procedure and diagnosis codes of pacemaker insertion followed by ablation, the cohort who underwent AVN ablation was identified. Patients hospitalization with any diagnosis of other type of arrythmia or epicardial ablation were excluded. Complications were defined as per the Agency for Health Care Research and Quality guideline. Results: Total AF ablation was noted to increase from 2005- 2011, and declined steadily from 2011–2014. In contrast, the number of AVN ablations increased from 4505 cases to 5175 (Figure 1). AVN ablation were mainly performed in elderly patient (mean age 72), and increasingly in patient with higher Charlson Commobidity index (0.9 to 1.7)and higher CHA2DS2-VASc score (2.8 to 3.7) (Table 1). An increasing trend in procedure complications but no significant change in mortalitywere observed with AVN ablation. Progressive increase in the length of stay and the hospitalization cost were also observed over the years with AVN ablation. Conclusion: AVN ablation is being performed at a steady volume, and increasingly in patients with multiple comorbidities. This trend although was not associated with increased mortality, it was associated with increased hospital complications. Funding Acknowledgement: Type of funding source: None